Multiple disease resistance against four fungal foliar diseases of rapeseed - Mustard - NARESH MEHTA; C.D. KAUSHIK, J.K. DANG, M.S. SANGWAN, (Indian Phytopathology, 2002)
Thirty-six Cruciferae [Brassicaceae] genotypes belonging to different brassicas were evaluated for resistance to Alternaria leaf blight (Alternaria brassicae), downy mildew (Peronospora parasitica), white rust (Albugo candida) and powdery mildew (Erysiphe cruciferarum) diseases during three consecutive crop seasons (1994-96) at Hisar. The stability of resistance of individual genotypes for each disease was established by calculating mean disease score (d) and standard deviation (s) over the years.Identification of genotypes with multiple disease resistance was done using these two parameters over the combined data. Seven varieties/genotypes (B. alba [Sinapis alba], B. carinata (HC-1), B. juncea (DIR-1507 and DIR-1522) and B. napus (GS-7027, Midasand Tower)) had stable and multiple disease resistance. In addition, 13 genotypes belonging to different species possessed a fair degree of stable multiple disease resistance but to a lesser extent. These genotypes can be exploited in breeding programmes for development of varieties with multiple disease resistance.